A construção científica: conteúdo e contexto da investigação sobre capital social na pesquisa da Região Metropolitana de Belo Horizonte - Joyce Gesuilo Gonçalves (2013)
This work studies social capital researches regarding the Pesquisa da Região Metropolitana de Belo Horizonte (BHSurvey), developed at Universidade Federal de Minas Gerais between 2001 and 2008. Its main goal was analyzing the development of this UFMG investigation, from the created contents and construction proccess. To achieve that, we studied the Social Sciences historical environment during the time preceding the Survey and the institutional questions involved in its creation. We delve further into the discussion about the procedures adopted by BHSurvey, focusing questions about social capital, which were included in the final survey of each research instalment. Analyses discuss data produced in relation to the teorethical aims of the study, i.e., data validity and contributions of context and content analyses to social capital discussion. Last, we present the weak point in measuring social capital, according to BHSurvey approach, given the data production used. We discuss also the importance of BHSurvey as a methodological revitalization and keystone to understanding the researches choices. This paper ends being an information source about the social capital, and points to the emanings achieved when we focus on science's construction, rather than its data.